MEASURING BLOOD OXYGEN AND HEART RATE WITH THE MAX 30100 PULSE OXIMETER SENSOR - Marian IONESCU; Ilie BORCOSI (Fiabilitate şi Durabilitate)
This paper presents a way to measure the blood oxygen concentration called SpO2 and the heart rate BPM, using a MAX-30100 pulse oximeter sensor. To visualize the value of Spo2 and heart rate BPM, a 16×2 LCD screen was used as a display. The MAX 30100 module and the LCD display connect to the Arduino Uno development board that ensures the acquisition, monitoring and display of the patient's health parameters